The literary culture of the Moriscos, 1492-1609 : a study based on the extant manuscripts in Arabic and Aljamía - Harvey, LP (1958)
That no one should hitherto have attempted to collect together in one place the evidence which is available on the subject of the literary culture of the Moriscos is scarcely surprising. The primary reason for such an omission has doubtless been the inferior nature of so much of what was written by the Moriscos, whether in Arabic or in aljamía; a secondary factor contributing to this neglect has been that these studies do not fall entirely within the purview of any one established discipline. It is clearly desirable that information about Morisco writings, whether in Arabic or aljamía should be brought together; this study is an attempt to fill this gap. An Introduction (pp. 1-26) examines and defines the terms Morisco and aljamía: Morisco, (somewhat improperly as is explained) is applied to the converted Muslims living on in Spain after 1492, aljamía is Spanish written in Arabic characters. The object of the present study is to investigate the literary culture of the Moriscos between 1492 and 1609 in the extant ms. sources, both Arabic and aljamiado. The study is divided into two parts, the first listing and discussing the sources of our knowledge of the literature of the Moriscos, the second analysing and interpreting these materials. Continued in thesis ...